AN EMPIRICAL STUDY ON CONSUMER BEHAVIOR TOWARDS E-MARKETING - Sharma, Dr. Tanuj; Sharma, Dr Neha; Uniyal, Dr Mahesh (The journal of contemporary issues in business and government, 2022)
With the advent of internet, it has created an integrally new experience for consumers regarding cluster of information, comparing the products with its price, quality, quantity and the possibility of purchasing through internet. As the literacy on internet increases the prospect of online marketing is also increasing in India. It has turned the entire world into a global village through advanced internet connect with which the online shopping has a major tributary in human being. And it has changed the way of consumers buying behavior of products and services through E-Marketing. This paper has been intended to examine the key consumer behavior and the relation among them ine- marketing perspective. The study was conducted in Bangalore City, Delhi and Emakulam district. The study was circumscribed to asample size of 200. This paper also give direction to improve delivery and advertising web-products & services to achieve objective of E-marketing and E-commerce in long run.